Determinant of Financial Management Behavior: Evidence From MSMES Gen-Z - Infante, Yusnita Octafilia Th. A. Y.; Mardika, Dhoni Rizky Widya (International Journal of Management and Digital Business, 2024)
Gen-Z is a contemporary generation characterized by a proclivity for modern thinking. The scale of the modernization trend can distance Gen-Z from a thrifty way of managing their finances. Understanding the determinants that can enhance the quality of financial management among individuals belonging to the Gen-Z demographic is crucial. The objective of this study is to investigate the impact of financial knowledge, personality factors, and locus of control on financial management behavior. The study specifically examined Micro, Small, and Medium Enterprises (MSMEs) owned by individuals from the Gen-Z generation in Salatiga. The study's sample size comprised 257 respondents. The data-gathering approach utilized in this inquiry was the use of a questionnaire. The study used the statistical method of multiple linear regression analysis. The results of this study indicate that individuals' financial management behaviour is significantly and positively influenced by their financial knowledge, personality attributes, and locus of control. These findings suggest that MSMEs should improve their understanding of financial matters, develop positive personal qualities, and cultivate a strong sense of accountability to accomplish successful financial management. MSMEs gen-z implementing effective financial management techniques are expected to demonstrate improved corporate management capabilities.